Pharmacokinetics of procaterol in thoroughbred horses. Issue 3 (5th November 2015) - Kusano, K.; Nomura, M.; Toju, K.; Ishikawa, Y.; Minamijima, Y.; Yamashita, S.; Nagata, S.
Abstract : Procaterol (PCR) is a beta‐2‐adrenergic bronchodilator widely used in Japanese racehorses for treating lower respiratory disease. The pharmacokinetics of PCR following single intravenous (0.5 μg/kg) and oral (2.0 μg/kg) administrations were investigated in six thoroughbred horses. Plasma and urine concentrations of PCR were measured using liquid chromatography–mass spectrometry. Plasma PCR concentration following intravenous administration showed a biphasic elimination pattern. The systemic clearance was 0.47 ± 0.16 L/h/kg, the steady‐state volume of the distribution was 1.21 ± 0.23 L/kg, and the elimination half‐life was 2.85 ± 1.35 h. Heart rate rapidly increased after intravenous administration and gradually decreased thereafter. A strong correlation between heart rate and plasma concentration of PCR was observed. Plasma concentrations of PCR after oral administration were not quantifiable in all horses. Urine concentrations of PCR following intravenous and oral administrations were quantified in all horses until 32 h after administration. Urine PCR concentrations were not significantly different on and after 24 h between intravenous and oral administrations. These results suggest that the bioavailability of orally administrated PCR in horses is very poor, and the drug was eliminated from the body slowly based on urinary concentrations. This report is the first study to demonstrate the pharmacokinetic character of PCR in thoroughbred horses.